2015
DOI: 10.1007/s12178-014-9254-7
|View full text |Cite
|
Sign up to set email alerts
|

The state of cartilage regeneration: current and future technologies

Abstract: It is clear that mature human articular cartilage does not have the innate ability to regenerate. Due to this, much effort has been put forth to work on bestowing this ability. While early data focused on more basic outcomes such as percentage of defect fill, the tissue formed was a "cartilage scar" or "hyaline-like" tissue. Even with more advanced technologies, it is clear that no current procedure is able to reconstitute the native structure and function of true hyaline cartilage. As research advancement has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
0
14
0
5
Order By: Relevance
“…Thus far, trials augmenting MFx with stem cells, growth factors, and cell scaffolds have all produced encouraging results. 13,15 BioCartilage (Arthrex Inc) contains desiccated, particulated allograft cartilage that is hydrated with platelet-rich plasma (PRP) and placed into contained cartilage defects where MFx has been performed. The purpose of this investigation was to evaluate the safety, biocompatibility, and efficacy of BioCartilage and leukocyte-reduced PRP for cartilage repair in a preclinical equine lateral femoral trochlear ridge model of full-thickness articular cartilage loss.…”
mentioning
confidence: 99%
“…Thus far, trials augmenting MFx with stem cells, growth factors, and cell scaffolds have all produced encouraging results. 13,15 BioCartilage (Arthrex Inc) contains desiccated, particulated allograft cartilage that is hydrated with platelet-rich plasma (PRP) and placed into contained cartilage defects where MFx has been performed. The purpose of this investigation was to evaluate the safety, biocompatibility, and efficacy of BioCartilage and leukocyte-reduced PRP for cartilage repair in a preclinical equine lateral femoral trochlear ridge model of full-thickness articular cartilage loss.…”
mentioning
confidence: 99%
“…However, BM-MSCs potentially have more chondrogenic capacity than adipose-MSCs and could be an ideal cell source for therapeutic application. 30,31 In this study, we loaded BM-MSCs on both gelatin and tissue scaffolds and found the formation of cartilage-like tissue and FIGURE 6. Histological and biochemical analysis of scaffolds after 3 weeks with or without TGF-β induction (control).…”
Section: Discussionmentioning
confidence: 81%
“…It has been shown that chemical crosslinking by EDC/NHS increases formation of covalent links between collagen-collagen and collagen-GAG by activating carboxyl and amine groups. 30,31 In this study, we loaded BM-MSCs on both gelatin and tissue scaffolds and found the formation of cartilage-like tissue and Based on the QPCR data, hBM-MSCs on the tissuederived scaffolds showed a significant increase in mRNA levels of chondrogenic markers including COL II and aggrecan, compared to those of gelatin scaffolds. Additionally, cell behavior is considerably influenced by the ECM microenvironment, where it provides a structural and mechanical support for the cells.…”
Section: Discussionmentioning
confidence: 93%
“…However, treatment with expanded cells is a necessarily more expensive 2-step procedure and is considered an advanced-therapy medicinal product that is subject to more rigorous regulatory requirements prior to clinical use. Cartistem injection (Medipost), an emerging technique currently undergoing a Food and Drug Administration phase I/II trial, utilizes culture-expanded allogenic umbilical cord blood MSCs that are surgically implanted with an HA scaffold into a microfractured defect (52). Conversely, these concentrates contain a lower number of MSCs in comparison with an expanded cell suspension and cannot be considered a homogeneous product (58), but rather a bone marrow or adipose tissue niche composed of different cell types (66).…”
Section: Emerging Technologies For Biologic Augmentation Procedures Fmentioning
confidence: 99%
“…Several in vitro and preclinical studies have demonstrated the ability of growth factors to provide symptom relief and enhance the quality of tissue fill when used in combination with cartilage regeneration . Their effects depend on many variables, including dose, formulation, delivery mode, treatment protocol, intraarticular environment, and integration . However, despite the vast knowledge about the effects of growth factors demonstrated in in vitro and preclinical models, there are very few completed human clinical trials.…”
Section: Emerging Technologies For Biologic Augmentation Procedures Fmentioning
confidence: 99%